Delving into psychosocial beliefs about lifelong learning: a comparison across educational levels. Issue 1 (2nd January 2023) - Van Nieuwenhove, Lisse; De Wever, Bram
ABSTRACT: Low-educated adults do not often engage in lifelong learning. The current study examines whether and how psychosocial beliefs about lifelong learning differ between adults with different levels of educational attainment. The Theory of Planned Behaviour, which focuses on three specific psychosocial beliefs (related to Perceived Behavioural Control, Perceived Social Norms, and Attitudes) is used as a theoretical framework. In total, 563 adults completed our survey. ANOVA-analyses were used to study between-groups differences. The results demonstrated that low- and medium-educated adults' experiences with psychosocial barriers are quite similar, except for power of control, since medium-educated adults experience more control over learning skills needed to participate. High-educated adults experience statistically significant more social pressure to engage in lifelong learning, especially from their work-related referents. In addition, high-educated adults experience statistically significant more control over their participation, specifically when it comes to control over skills necessary to participate in learning. Low-and medium-educated adults do show positive attitudes towards learning, but high-educated adults' attitudes are statistically significant more positive. Follow-up, qualitative studies could provide in-depth insight into these determinants. Additional understanding of the three psychosocial barriers could help educational institutions and policy makers to appropriately attract and support adult learners.